Effect of catch-up sleep on obesity in Korean adolescents: a nationwide cross-sectional study - Choi, Youngha; Kim, Sujin; Lee, Myeongseob; Lee, Hae In; Song, Kyungchul; Suh, Junghwan; Chae, Hyun Wook; Kim, Ho-Seong; Kwon, Ahreum (Frontiers in Pediatrics, 2023)
Background Adolescents have weekday/weekend sleep discrepancies and may compensate for weekday sleep debt through sleep extension on weekends. Objective We investigated the effects of total sleep duration on weekdays/weekends on obesity and determined if weekend catch-up sleep has an ameliorating effect on obesity in Korean adolescents. Methods Using data from the KNHANES VII, 1,306 middle and high school students were assessed for total sleep duration on weekdays, weekends, and the entire week, as well as weekend sleep extension. Participants were classified into four groups according to weekend sleep extension. Results Total sleep duration and weekend sleep duration were negatively associated with body mass index z-score. Increased weekend sleep duration and sleep extension on weekends decreased the relative risk of overweight/obesity with each 30 min increment, reducing the risk by a factor of 0.39 and 0.93, respectively. The risk of overweight/obesity in adolescents who slept less than 6 h on weekdays increased by a factor of 1.93 when they slept for less than 3 h on weekends. Conclusion Weekend catch-up sleep had a negative dose-dependent association with obesity in Korean adolescents. Sleeping longer on weekends may be associated with a decreased risk of obesity, even if the adolescent obtains less sleep during weekdays. However, further prospective studies are needed to establish the causality between extended weekend sleep and obesity.